العوامل المؤثرة في مقاومة القص المتبقية في الترب السيلتية (Latakia University Journal -Engineering Sciences Series, 2019)
تعد مقاومة القص المتبقية معيارا هاما من المعايير المطلوبة التي على أساسها يتم تقييم توازن المنحدرات ومقاومة التربة وسلوكها, وقد ركز هذا البحث على دراسة مجموعة من العوامل التي تؤثر سواء على قيمة مقاومة القص المتبقية أو على زاوية الاحتكاك المتبقية للترب السيلتية القابلة للانزلاق, وذلك اعتمادا على نتائج عدد كبير من التجارب المخبرية التي أجريت على أنـواع مختلفة من تربة السيلت بحالات إشباع وتحميل مختلفة . يمكن الاستنتاج وفقاً لنتائج التجارب والاختبارات التي أجريت على حالات متنوعة من العينات السيلتية أن ثمة كثيراً من المؤثرات والعوامل تؤثر بشكل واضح على قيمة مقاومة القص المتبقية في السيلت منها قيم الحمولات الناظمية ودرجة الإشباع والتحميل المسبق وتشوه القص وخشونة محتوى التربة من الحبيبات الرملية. The residual shear resistance is usually used as a criterion on which the issues of slope stability, soil resistance and behavior are evaluated. This research concentrates on the study of a group of factors affecting the residual shear force or residual shear angle for silting soils prone to sliding, taking into account the results of a great number of laboratory tests of different types of silt in different situations of saturation and loading. According to the results of tests conducted on samples of silt in different situations, tt can be concluded, that there are many effects and factors that affect the value of the residual shear resistance of silt, such as the value of applied normal pressure, the degree of saturation, pre-loading, shear displacement, and roughness of the soil content of grains of sand.